(3TQM fgL GdHdGZIs - (3CHi MGeO YRGdOjf YHO GdMejO Hf gHg Gddg Hf eMeO Hf GdMSjf Hf CHi GdMOjOs; (3GdTQja GdeQJVi CHj GdbGSe Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje CHhGdbGSe,J (B436 (3g` s ((3YHOGdHGbi GddGghQi hGejQ ejQRG s)
(3ChdgG (B:s
(3hHYO aEf eQGSe Gdehdi GhRjQ CHj WGdH eMeO Hf CMeO Hf eMeO GdYdbfei HTQM fgL GdHdGZI HGOQ Edi Pdc s
(3BNQgG (B:s
(3Ke jeQhf Ydi gPG GdcdGe GdeTMhf cdg HgPg GdUag Ydi CdWa hLgg hGfUM hLg hCQTa YHGQI hCOb eYfi hCMSf ebUO Je s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B21 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1991s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs